Drug Addiction - Zhao, Fang; Li, Meng (IntechOpen, 2018)
This edited volume is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of drug addiction. The book comprises single chapters authored by various researchers and edited by an expert active in the pertinent research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on drug addiction, and opens new possible research paths for further novel developments.